2019
DOI: 10.1017/wsc.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Interference of turnipweed (Rapistrum rugosum) and Mexican pricklepoppy (Argemone mexicana) in wheat

Abstract: Turnipweed [Rapistrum rugosum (L.) All.] and Mexican pricklepoppy (Argemone mexicana L.) are increasingly prevalent in the northern cropping regions of Australia. The effect of different densities of these two weeds was examined for their potential to cause yield loss in wheat (Triticum aestivum L.) through field studies in 2016 and 2017. There was 72% to 78% yield reduction in wheat due to competition from R. rugosum. Based on the exponential decay model, 18.2 and 24.3 plants m−2 caused a yield reduction of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 28 publications
3
23
1
2
Order By: Relevance
“…Differences observed between growing seasons were probably related to differences in the competitive capacity of wheat cultivars and prevailing environmental conditions during the growing season. Our results were similar to those obtained by Eslami et al (2006) and Manalil and Chauhan (2019) in R. raphanistrum and R. rugosum, respectively, although they used a wider range of weed densities (0 to >60 wild radish plants m -2 and 0 to >45 R. rogosum plants m -2 ), which could indicate that feral radish is more competitive than wild radish and R. rugosum, two important Brassicaceae weeds. Data fit the model YL = 46.26D/(1 + 46.26D/62.19) (winter wheat) and YL = 14.54D/(1 + 14.54D/74.44) (spring wheat).…”
Section: Wheatsupporting
confidence: 89%
See 1 more Smart Citation
“…Differences observed between growing seasons were probably related to differences in the competitive capacity of wheat cultivars and prevailing environmental conditions during the growing season. Our results were similar to those obtained by Eslami et al (2006) and Manalil and Chauhan (2019) in R. raphanistrum and R. rugosum, respectively, although they used a wider range of weed densities (0 to >60 wild radish plants m -2 and 0 to >45 R. rogosum plants m -2 ), which could indicate that feral radish is more competitive than wild radish and R. rugosum, two important Brassicaceae weeds. Data fit the model YL = 46.26D/(1 + 46.26D/62.19) (winter wheat) and YL = 14.54D/(1 + 14.54D/74.44) (spring wheat).…”
Section: Wheatsupporting
confidence: 89%
“…Similar results were observed due to the interference of the grass weeds, Avena fatua and Lolium persicum (Holman et al 2004, Guillen-Portal et al 2006. However, the Brassicaceae species Rapistrum rugosum reduce wheat yield mainly due to a reduction in the number of spikes per area and grains per spike but, unlike our results, the weed did not affect the grain weight (Manalil and Chauhan 2019). The adjusted rectangular hyperbolic functions (R 2 = 0.93 and 0.86) showed that feral radish reduced the wheat yield per unit by 46.3 and 14.5 % at low weed density (parameter I), and by 62.2 and 74.4 % when the density approached infinity (parameter A) for winter (F = 204.15; P < 0.0001) and…”
Section: Wheatsupporting
confidence: 87%
“…Wheat can be in plant rotation with Argemone mexicana. However, the wheat yield losses of 17% and 22% have been noticed [64]. Crambe abyssinica can be cultivated in rotation with soybean [65] to suppress the growth of weed and fertilize the soil.…”
Section: Land Occupationmentioning
confidence: 99%
“…and Mexican poppy ( Argemone mexicana L.) are three major winter weeds of agricultural landscapes across the world 1 8 . These weeds are quite predominant under the conservation agricultural systems of Australia and can invade agricultural landscapes and environments rapidly due to their superior competitiveness, high seed production ability, and their biological features 2 , 9 , 10 . Rapistrum rugosum and A. mexicana are generally confined to winter growing conditions, exhibiting a high level of competitiveness and reproductive potential, though they can emerge and set some seeds during the post-winter season 2 , 7 , 10 12 .…”
Section: Introductionmentioning
confidence: 99%